Home-Country Institutional Pressure and Foreign Divestment: Evidence from Developed-Country Multinationals in China - Wang, Qihu; Gong, Yue; Gao, Yilan (Asia Pacific Economic and Management Review, 2025)
In recent years, advanced economies have increasingly adopted restrictive outward-investment measures, creating unprecedented institutional pressures on developed-country multinational enterprises (DMNEs). Yet DMNEs’ responses, particularly foreign divestment decisions, remain heterogeneous and underexplored. Building on the institution-based view and investment opportunity perspective, this study investigates how home-country institutional pressure influences DMNEs’ divestment from China and how investment opportunities moderate this relationship. Using a panel dataset of DMNEs listed in China from 2018 to 2024, we find that home-country institutional pressure significantly increases foreign divestment, and that this effect is amplified when firms face abundant investment opportunities. These findings extend international business research by (1) positioning home-country institutional pressure as an active driver rather than a background condition of DMNE strategy, and (2) identifying investment opportunities as a critical boundary condition shaping firm responsiveness. The study also offers managerial and policy insights into managing strategic choices under rising geopolitical and institutional constraints.